Peran Kepala Madrasah Terhadap Pendidikan Ahklak Santri Di Madrasah Roudlotut Tholibin - Ahmad Zainul; Devy Habibi Muhammad (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to analyze the role of the Headmaster of Madrasah Roudlotut Tholibin in shaping the moral character of students and the factors supporting the success of moral education within the institution. A descriptive qualitative approach was employed, utilizing a naturalistic research method. Data was gathered through library research and fieldwork interviews with relevant informants. The findings reveal that the Headmaster plays a central role in establishing the vision and mission of education, leading by example, and developing a curriculum that integrates moral education. Key supporting factors identified include a structured curriculum, extracurricular activities, the use of media and technology, as well as active involvement from parents and the community in the educational process. Moreover, the strategies employed in character development, such as role modeling, habitual practice, advice (mauidzotul hasanah), discipline, and the cultivation of independence, have proven effective in shaping students' character. This study recommends that educational institutions continue to innovate in their moral education programs, strengthen collaboration with parents, and optimize the use of technology.